Explore The Potential Community-Based Tourism of Cikadu Edutourism as A Tanjung Lesung Bufferzone Area - Filda RahmiatI; Felix Goenadhi (Journal of the Community Development in Asia (JCDA), 2022)
The purpose of this research is to determine the possibility for Cikadu Tourism Village, Bufferzone Tanjung Lesung, to transition to community-based tourism through the use of the 4C model (Conservation, Community, Culture, and Commerce). In-depth interviews and interactive observations were used to acquire qualitative data. This study focuses on Cikadu Tourism Village, Tanjung Lesung's buffer zone. The findings of this study show that the Cikadu Tourism Village, Bufferzone Tanjung Lesung, has the potential to develop into a community-based tourism village. The community is eager to collaborate in order to conserve existing culture through the preservation of regional dances, the production of batik employing regionally distinctive designs, and the prudent use of existing natural resources. The natural splendor of the accessible coastal areas provides an excellent opportunity for tourist growth. However, Cikadu Tourism Village, Bufferzone Tanjung Lesung, has a long way to go in terms of establishing community-based sustainable tourism. Additionally, it must carry out tourist value chain (TVCA) operations in order to generate competitive advantages. Keywords: Community-based tourism, culture, commerce, conservation, community, pandemic, and sustainable tourism.